El desempleo y su influencia en el comercio informal en la ciudad de Machala. - Flores Mayorga, Christian A. (2015)
This research has as main objective to analyze the informal trade from local unemployment according to the research of some important factors that make unemployed people looking for a way to be used and cover their basic needs , temporary unemployment statistics were used in the city of Machala , based on informa¬tion provided by the various local public enterprises, and looking from these statistics form a regression mo¬del , should determine what are the most important features in order to explain the level of unemployment and its prevalence in the informal sector. To this has been done has been done a research tour of some local publications internationally and discusses the relationship of this foundation.